2017
DOI: 10.1038/ijo.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Time spent in sedentary posture is associated with waist circumference and cardiovascular risk

Abstract: Time spent in sedentary posture is associated with waist circumference and cardiovascular risk. International Journal of Obesity. Permanent WRAP URL:http://wrap.warwick.ac.uk/86976 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 51 publications
0
37
1
3
Order By: Relevance
“…Fifteen papers reported no significant association between sedentary time and HDL‐C . Sedentary time and low‐density lipoprotein cholesterol (LDL‐C) were positively associated in two papers , neither of which was adjusted for PA. Twelve papers found no significant association between sedentary time and LDL‐C . The association between sedentary time and total cholesterol was positive in one paper ; however, no adjustment was made for PA.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Fifteen papers reported no significant association between sedentary time and HDL‐C . Sedentary time and low‐density lipoprotein cholesterol (LDL‐C) were positively associated in two papers , neither of which was adjusted for PA. Twelve papers found no significant association between sedentary time and LDL‐C . The association between sedentary time and total cholesterol was positive in one paper ; however, no adjustment was made for PA.…”
Section: Resultsmentioning
confidence: 97%
“…From the included papers, 10 came from NHANES , three from AusDiab , three from the Whitehall II Study , two from HSE , two from RISC study and one each from the Generation 100 Study , EVIDENT study , Leuven Longitudinal Study on Lifestyle, Fitness and Health (LLSLFH) , Swedish CArdioPulmonary bioImage Study (SCPIS) , International Physical Activity and the Environment Network Adult Study , New Method for Objective Measurements of Physical Activity in Daily Living study , Hispanic Community Health Study/Study of Latinos and Canadian Health Measures Survey . The remaining 16 papers were all individual/stand‐alone studies . For the meta‐analysis, the aggregated sample size and mean age ( n , years) for the five included health markers were fasting glucose (25,356, 41.6), fasting insulin (10,474, 37.0), triglycerides (26,562, 42.4), HDL‐C (29,582, 46.1) and waist circumference (16,842, 44.6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rise in the prevalence of such activities has led to the notion of a major shift in posture allocation from standing in favor of sitting on a population basis. With this belief has come a myriad of correlative analyses showing a positive relationship between sitting time and cardiometabolic disease risk (Henson et al, 2016; Young et al, 2016; Tigbe et al, 2017). In addition, studies have now shown that obese individuals spend significantly more time sitting and less time standing than their lean counterparts (Levine et al, 2005; Johannsen et al, 2008).…”
mentioning
confidence: 99%